Piracy in light of marine insurance law with a view of ransom payments - Gliha, Dino (Array, 2018)
After the 2008 Somali attacks, piracy has gained significant popularity among scholars. However, despite lots of ongoing debates and written papers in the last decade, some crucial issues have been left unresolved, starting from the definition of piracy. When discussing piracy within the context of marine insurance, certain specific characteristics of marine insurance law should be taken into consideration. Namely, international law definition, criminal law definition and other definitions of piracy cannot properly satisfy the need of marine insurance law. After the proper understanding of piracy within marine insurance law is determined, there are some other important issues that need to be discussed. Certainly, one is categorization of piracy as a peril. Question whether piracy is a marine peril or a war peril? Further on, one of the most discussed issue of modern piracy are ransom payments. Can they even be considered legal? If yes, are they recoverable from marine insurers and on which basis? Answers to previously mentioned questions will be given in the following paper.